Proceedings of the 1st Public Health International Conference (PHICo 2016) 2017
DOI: 10.2991/phico-16.2017.79
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Protozoa Infections and Associated Risk Factors in Rural Community of Samosir Island Indonesia

Abstract: Abstract-Intestinal protozoa infections are still a major health concern in tropical countries and considered one of neglected tropical infections. Giardia lamblia as one of the human protozoa can cause significant morbidity. It is associated with lack of personal hygiene and environmental sanitation, such as inadequate toilet, lack of hand washing habit, unimproved water supply, and insufficient handling of foods. Some other protozoa such as Balantidium coli and Blastocystis hominis are correlated with the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…In a study conducted by Sungkar on Sumba, B. hominis infection was 34.4% and Giardia lamblia 4.5% 1 . And a study on Samosir Island which received 23.1% positive samples of protozoa with 4.9% B.hominis infection and G. lamblia at 12.2% 6 . It can be concluded that the prevalence of B.hominis on Mandangin Island is higher than in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Sungkar on Sumba, B. hominis infection was 34.4% and Giardia lamblia 4.5% 1 . And a study on Samosir Island which received 23.1% positive samples of protozoa with 4.9% B.hominis infection and G. lamblia at 12.2% 6 . It can be concluded that the prevalence of B.hominis on Mandangin Island is higher than in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…3 Angka kejadian akibat Giardia lamblia memiliki bervariasi, salah satu penelitian di Pulai Samosir, Sumatera Utara didapatkan infeksi akibat G. lamblia sebanyak 12%. 4 Kriptosporodiosis akibat Cryptosporidium sp. memiliki angka insidens sebanyak 77.7% dari semua diare kronik di Jakarta.…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang dilakukan terhadap 368 penduduk desa di Pulau Samosir pada tahun 2015 didapatkan bahwa kebiasaan buang air besar (BAB) sembarangan, kebiasaan hidup untuk mencuci tangan yang baik dan benar, dan konsumsi air minum yang belum diolah menunjukkan korelasi yang kuat dengan kejadian infeksi protozoa sebesar 23,1% (Yulfi et al, 2017). Di Sumatera Barat, angka kejadian infeksi protozoa masih cukup tinggi.…”
Section: Pendahuluanunclassified